(untitled) (Revista de Ciências Agroveterinárias, 2021)
Solanum diploconos (Mart.) Bohs („guava tamarillo”) and Solanum corymbiflorum (Sendtn.) Bohs („hardy tamarillo”) are wild relatives to subtropical, orchard, small tree – Solanum betaceum Cav. (called simply „tamarillo”). Both these species create edible fruits, but they have not been cultivated widely so far as fruit trees. However, each one of these species has valuable features. Solanum corymbiflorum is quite hardy to frost, deciduous and early blooming both in fenological year time as well as in its lifespan but has untasty fruits. Solanum diploconos has quite good tasting fruits and it is pest and disease resistant. This work has been an attempt to connect their best features in hybrids to create new, potentially commercial cultivars to grow as fruit plants. Three types of hybrids were created: F1 hybrid type – Solanum corymbiflorum × Solanum diploconos, BC1 backrossing type - (Solanum corymbiflorum × Solanum diploconos) × Solanum corymbiflorum and the second BC1 backcrossing type – (Solanum corymbiflorum × Solanum diploconos) × Solanum diploconos. Out of the numerous variable individuals within each type, we selected three very valuable from an agronomic point of view cultivars (Solanum ’Lynn’, ’Pinczow Springs’ and ’Iwona’). The work with crossing and selecting the next cultivars will be continued.